1998
DOI: 10.3109/08880019809018311
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma: Problems and Perspectives from India

Abstract: This study examined the salient clinical and epidemiological characteristics of retinoblastoma (RB) in India, thereby highlighting the problems encountered there. The epidemiological characteristics of 296 patients with RB over 8 years were evaluated using hospital records and postal follow-ups. Unilateral disease was seen in 61.8% of patients. The overall median age at presentation was 3.5 years (3.5 years for unilateral RB and 1.0 years for bilateral RB). The male/female ratio was 1.4:1. The median duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
33
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 24 publications
10
33
3
Order By: Relevance
“…24 Sahu et al in their retrospective study of 296 affected patients with retinoblastoma, over an 8 years period, in Mumbai, India, also found a predominance of advanced-stage disease with 74.5% presenting with Reese-Ellsworth group IV and V disease. 20 These findings are supported by our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…24 Sahu et al in their retrospective study of 296 affected patients with retinoblastoma, over an 8 years period, in Mumbai, India, also found a predominance of advanced-stage disease with 74.5% presenting with Reese-Ellsworth group IV and V disease. 20 These findings are supported by our study.…”
Section: Discussionsupporting
confidence: 82%
“…As survival in patients with retinoblastoma is inversely related to the stage of the disease at presentation, [20][21][22][23][24] we carried out this study to determine the stages of retinoblastoma in our patients at presentation and their relation to outcome. This will serve as baseline data for further studies and help plan interventions for improvement in survival.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the majority of patients (64%) presented with unilateral retinoblastoma and the remaining (36%) are bilateral. This figure is similar with findings from several Asian countries (Sahul et al, 1998;Patikulsila et al, 2001). In this study, there was not much difference in the number of retinoblastoma between male and female; male to female ratio of 1.3:1.…”
Section: Discussionsupporting
confidence: 82%
“…Only animals in the Y79 tumor group had tumors that appeared to mimic the aggressive, rapidly growing, metastatic retinoblastomas only occasionally observed in North America and Europe but more commonly seen in Mexico, Central and South America, Saudi Arabia, and India. 29 The WERI-Rb animal model behaved like patients with nonmetastatic retinoblastoma more commonly seen in Europe and North America.…”
Section: Discussionmentioning
confidence: 99%